Peningkatan Pendapatan Petani Melalui Diversifikasi Dan Intensifikasi Tanaman Hortikultura Di Lahan Kering Desa Gumantar Kabupaten Lombok Utara - Jayaputra Jayaputra; Nurrachman Nurrachman; Bambang Budi Santoso (Universitas Mataram, 2021)
Planting diversification with horticultural crops in the dry land area of North Lombok Regency is an effort to increase the planting index (IP) which is supported by appropriate cultivation technology and sufficient water availability to support plant growth. It was hoped that the increase in the cropping index in dry land areas will trigger an increase in community welfare, particularly an increase in farmers' income. Horticultural development is intended to provide added value to increasing farmers' income. Gumantar Village, Kayangan District, North Lombok Regency is one of the areas that has dry land which is quite potential for horticultural development. The problems faced by farmers in these areas include the low level of knowledge and skills of farmers, especially in the management of horticultural commodities. So far, farming activities were still traditional and the level of farmer participation was still relatively low. To overcome these problems, it was necessary to transfer innovation technology through the development of environmentally friendly horticultural crops with the application of Good Agricultural Practices and production management in accordance with natural resource conditions. Counseling and training as well as demonstration plots using the Participatory Action Research method related to horticultural cultivation technology have been carried out in Amor-Amor hamlet, Gumantar village in July-December 2019. This community service activity is considered quite successful as seen from the enthusiasm and persistence of the participants in attended counseling, training, and demonstration plots (cultivation of tomatoes and golden melons). The results of the demonstration plot showed a significant increase both in the aspect of crop productivity and increased income per unit area of arable land. Continuous assistance from all parties, especially the local government was highly expected for the sustainability of horticultural commodity development efforts in order to increase the income of dry land farmers